From Words to Action: Incorporation of Sustainability in Architectural Education - Hassanpour, Badiossadat; Atun, Resmiye Alpar; Ghaderi, Soheil (Mdpi, 2017)
Schools of architecture play a major role in motivating and inspiring students to gain competencies in sustainability through pedagogical practices. However, at the operational level, the incorporation of sustainability within architectural programmes needs to be integrated into both the curricula and teaching methods. There are few studies on how architectural programmes' curricula and pedagogical practices can be institutionally articulated, as well as on how the required coherency among components can be empowered operationally. Since the interrelation of the courses form the structure of the curricula and provide certain inputs for the students' knowledge and skill, any operational risk can harm the quality assurance. Therefore, an operational framework aimed for a coordinated incorporation of sustainability in architectural programmes is required. In order to achieve this, scrutinising substantial equivalence programmes could provide constructive outcomes for the improvement of the existing programmes and future experiences for students. In order to determine the articulation of sustainability issues in architectural education, in this research, a recently accredited school in the Eastern Mediterranean region was chosen as a case study. The study includes an analysis of course descriptions, teaching methods, and teacher and student perceptions about the incorporation of sustainability into the courses. Also, jury sessions' evaluation criteria are assessed as a pedagogical tool. Then, the horizontal and vertical articulation of courses within the curricula and their coordination were studied accordingly. The findings reveal that horizontal and vertical relations between different course types that share similar learning objectives are very important. However, this relation and continuum should be perceivable by students, tutors, and the relevant stakeholders; otherwise, any attempt would remain superficial. Accordingly, the association of sustainability with pre-defined evaluation criteria for grading is very important. The methodological tools and lessons from this study can assist young architecture programmes with the incorporation of sustainability into their programme without changing its spirit, through the coordination of courses within curricula and adopted pedagogical tools.
Keywords: accreditation; architectural education; assessment tool; sustainability; curriculum